Corporate CRM - The Influential Factors and Difficulties Facing the FMCG Industry: A Case Study of Procter & Gamble - Kao, Yu Chieh (2007)
Customer Relationship Management (CRM) is a widely used business management method in today's industry. In order to attract more new customers and squeeze greater revenues from the ones on hand, companies are seeking a comprehensive CRM solution that can facilitate the complex business rules and processes within organizations and at the same time enhance customer data for better customer segmentation and profitability measurement for organizations' decision making.